Social aspects role and the behavior of drinking water among students in a private university - Sitti Nur Djannah; Ratu Matahari (International Journal of Evaluation and Research in Education (IJERE), 2020)
Lack of consuming drink water can cause many effects on the body. The long term effects of less consuming water dangerous for health. The diseases related to the less consuming water are respiratory tract infections, gastrointestinal disease, urinary infections, cancer, diabetic, kidney disease, and also others metabolic disorders. Those diseases affected to the financial burden due to this situation. It happens because of some factors, many studies mentioned about the behavior of drinking water among adolescents in school affected by some sociodemographic and behavioral factors. This study shows that most of respondents have a bad habit to keep their health kidney it is evident that the majority of respondents have urine color that tends to concentrated which is categorized as unhealthy urine. The limitation of the study was not measure the amount of drink water consuming for each respondents per day.